Development of selective real-time PCR (SPCR) asays for the detection of K103N resistance mutation in minor HIV-1 populations - Seleka, Mpho Maria (Stellenbosch : Stellenbosch University, 2011)
Thesis (MScMedSc)--Stellenbosch University, 2011.